2018
DOI: 10.17816/snv201873115
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and biological activity of peat deposits of oligotrophic bog

Abstract: The article presents the results of the main general technical, physical and chemical, microbiological and biochemical properties of the oligotrophic bog (Tomsk Region). It shows that peat oligotrophic bog belong to low-ash (2,3-10,9%), high - acid (2,2-3,6 units of pH), with the degree of decomposition - 20-50%. The authors find that the concentration of ammonium nitrogen increases with depth, and nitrate - decreases. The largest accumulation of mobile connections of phosphorus observed in the upper layer of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…After the samples were decomposed with mineral acids, higher (p < 0.05) phosphorus concentrations (0.11-0.42%) were determined. These results of our research coincide with the trend found in works of other authors [27,28]. Analysing aqua regia extract data, it was observed that higher amounts (p < 0.05) of phosphorus are present in the samples with lower humification: for example, in H5, there is 0.42% P 2 O 5 (MTL, sample 6), while H8 includes only 0.14% P 2 O 5 (sample 4 EKD).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…After the samples were decomposed with mineral acids, higher (p < 0.05) phosphorus concentrations (0.11-0.42%) were determined. These results of our research coincide with the trend found in works of other authors [27,28]. Analysing aqua regia extract data, it was observed that higher amounts (p < 0.05) of phosphorus are present in the samples with lower humification: for example, in H5, there is 0.42% P 2 O 5 (MTL, sample 6), while H8 includes only 0.14% P 2 O 5 (sample 4 EKD).…”
Section: Resultssupporting
confidence: 92%
“…Differences obtained in the analytical results could be explained by the individual composition and structural features of the composition of peat, which depend on the botanical composition, the degree of humification, the formation and the environmental conditions. In summary, it can be stated that the results of samples from different peatlands, when compared to each other, differ, and this is also described in studies of other researchers [15,19,[27][28][29]. The unevenness of the chemical composition of peat could be explained by the fact that it contains organic and mineral parts and high moisture content.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation